The role of research in promoting human rights and citizenship education in Croatia - Spajić-Vrkaš, Vedrana (Array, 2012)
The first educational programmes that promoted learning for human rights and citizenship from preschool to secondary school level were developed in Croatia by the end of 1990s as the Government’s response to the UN Decade for Human Rights Education. As the Ministry of Education approved only elementary school programme to be implemented as an “optional integrative content”, it actually devalued citizenship as the goal of education. Such status remained unchanged for over a decade despite the fact that active citizenship was recognised by laws on education as the key to democratic development. In 2010 it was finally adopted as an obligatory cross-curricular theme in the competence-based National Framework Curriculum. However, due to the lack of political will and of public administration support the status of citizenship education de facto remained unchanged. The changes began upon the presentation of findings from a series of studies on citizenship preparation among elementary and secondary school students. The studies made it clear that Croatian youth was not prepared for the challenges of a transitional democracy. Their knowledge on human rights, democracy and citizenship was less than moderate, especially in those fields that are crucial for their acting as emancipated and engaged citizens. The findings on their civic and political culture portray them as passive, cynical and self-centred members of the polity and the society. Very few trust political and public institutions and their actors ; a small number of them have ever worked for the benefit of their communities ; many are socially distanced towards all neighbouring national and religious groups and a considerable number fear that Croatian accession to the European Union would imperil national identity, sovereignty and wealth. Finally, the findings on students’ opinions about learning citizenship confirmed that schools are less important in political and civic socialization than the family and the media. Citizenship, human rights and democracy are learned in Croatian school through several existing subjects but it turned out that the choice of teaching contents, methods and strategies is more duty-oriented than emancipatory. The failure of schools to prepare their students for an empowered, engaged and self-expressive type of citizenship were found to be linked to a lesser use of active, participative and inquiry-based learning methods, to the avoidance of dealing with controversial issues which improve multiperspectiveness and critical thinking, and to underdeveloped school-community cooperation programmes. These results incited the drafting of the first competence-based Citizenship Education Curriculum for Croatian schools. It aims at preparing the student for active citizenship at three levels: the school and local community ; the national community ; and the European and global community. For each educational cycle civic competence is defined in terms of knowledge and understanding, skills and dispositions, and values and attitudes. These dimensions are further defined in relation to the five dimensions of active citizenship: legal, political, social, inter/cultural, economic and environmental. The curriculum will soon be opened for public review and pilot-implemented in selected schools.